2022
DOI: 10.3389/fphar.2022.920201
|View full text |Cite|
|
Sign up to set email alerts
|

Xiongshao Zhitong Recipe Attenuates Nitroglycerin-Induced Migraine-Like Behaviors via the Inhibition of Inflammation Mediated by Nitric Oxide Synthase

Abstract: Migraine is a major cause of disability worldwide, particularly in young adults and middle-aged women. Xiongshao Zhitong Recipe (XZR) is a traditional Chinese medicine prescription used for treating migraine, but its bioactive components and therapeutic mechanisms remain unclear. We aimed to confirm the therapeutic effect of XZR on migraine and to determine the possible mechanism and bioactive components of XZR. Here, a sensitive UHPLC-LTQ-Orbitrap MS assay was carried out to analyze the ingredients of XZR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Our results suggesting that the CIHE attenuates the biomarkers such as MMP9[16], TNF-α[26], NFkB [27], IL-1β[28], CGRP [29], and iNOS [30] are involved in the migraine attack which represented in (Fig. 1).…”
Section: Discussionmentioning
confidence: 82%
“…Our results suggesting that the CIHE attenuates the biomarkers such as MMP9[16], TNF-α[26], NFkB [27], IL-1β[28], CGRP [29], and iNOS [30] are involved in the migraine attack which represented in (Fig. 1).…”
Section: Discussionmentioning
confidence: 82%
“…Herbal treatment has the advantages of holistic conditioning, multi-targeting, and long-lasting effects, which are conducive to individualized and fine-tuned treatment for migraine patients (58)(59)(60). In 22 years, Yang et al (61) showed that in a rat model of nitroglycerin (NTG)-induced migraine, the Chinese herbal formula Xiongshao Zhitongfang (XZR) regulated NO, 5-HT, CGRP, and SP to normal levels, while inhibiting mast cell degranulation and the release of inflammatory factors, which resulted in attenuation of migraine symptoms. In addition, in a homozygous rat model, rhubarb extract from the traditional Chinese medicine Rheum palmatum also downregulated the inflammatory response and alleviated migraine via the cGMP-PKG pathway (62).…”
Section: Discussionmentioning
confidence: 99%
“…Radix Angelica Sinensis and Chuanxiong Rhizoma as major herbal ingredients of the FSS formula possessed blood nourishment, wind elimination, and pain alleviation in TCM perspectives (Huang et al, 2020). Furthermore, modern medical studies reported that these two Chinese medicines had anti-nociceptive and anti-inflammatory activities (Wang et al, 2020;Li C. et al, 2022). Tetramethylpyrazine (ligustrazine) from Chuanxiong Rhizoma showed an anti-inflammatory effect on cells by regulating related signaling pathways such as nuclear factor kappa-B (NF-κB) and PI3K/AKT (Zheng et al, 2013;Zhang et al, 2020;Huang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, a single emulsion solvent evaporation method was used to prepare CS-AL NPs containing FSSO. In the nano-emulsion, AL was one type of hydrophilic polymer functioning as a wall-forming material for protecting loaded volatile substances; moreover, CS and calcium chloride (CaCl 2 ) are crosslinked with AL to produce hydrogel for gelification (Li S. et al, 2022).…”
Section: Introductionmentioning
confidence: 99%